Aplicação de indicadores de sustentabilidade da rede INSTO/UN Tourism em municípios brasileiros: proposta baseada na utilização de dados abertos - Bortolotto, João Pedro Zanella (My University, 2025)
Adopting sustainability as a fundamental premise for the development of the sector, the Brazilian government classifies over 2.000 municipalities with some level of tourist interest. Despite this, to date there is no effective mechanism in the country for monitoring the sustainability of tourism management in all these municipalities. Considering this situation, the research sought to assess the possibility of using open data to build sustainability management indicators for municipalities, with reference to the monitoring focuses proposed by the UN Tourism International Network of Sustainable Tourism Observatories (INSTO). It therefore analyzed indicators used internationally and explored open databases in an attempt to identify equivalents or inputs for the construction of indicators applicable to the national reality. To this end, it carried out documentary research, with the support of a multidisciplinary panel of experts to identify sources and validate the proposed indicators. As a result, it was able to propose a set of indicators, which would enable the monitoring of 9 of the 11 focuses, and a total of 46 indicators out of the 186 indicators proposed by the INSTO Network. [resumo fornecido pelo autor]
Adotando a sustentabilidade como premissa fundamental para o desenvolvimento do setor, o governo brasileiro classifica mais de 2.000 municípios com algum nível de interesse turístico. Apesar disso, não existe até o momento no país um mecanismo efetivo de monitoramento da gestão da sustentabilidade do turismo que acompanhe todos esses municípios. Considerando essa situação, a pesquisa buscou avaliar a possibilidade de utilizar dados abertos para construir indicadores de gestão da sustentabilidade para municípios tendo como referência os focos de monitoramento propostos pela Rede Internacional de Observatórios de Turismo Sustentável (INSTO) da ONU Turismo. Diante disso, analisou indicadores utilizados em nível internacional e explorou bases de dados abertos procurando identificar equivalentes ou insumos para a construção de indicadores aplicáveis a realidade nacional. Para isso, realizou uma pesquisa documental, contando com o apoio de um painel de especialistas multidisciplinar para identificar fontes e validar os indicadores propostos. Com isso, conseguiu propor um conjunto de indicadores, o qual permitiria o monitoramento de 09 dos 11 focos, em um total de 46 indicadores dos 186 indicadores propostos pela Rede INSTO. [resumo fornecido pelo autor]
Keywords: Turismo sustentável; Sustentabilidade; Turismo - Brasil; Sustainable tourism; Sustainability; Tourism - Brazil